Gender Effects in Dictator Game Giving: Women Favour Female Recipients - Maximilian Baltrusch; Philipp Christoph Wichardt (Center for Economic Studies and ifo Institute (CESifo), 2018)
Allowing for a free choice of the recipient's gender in a dictator game (N = 508), we find that women show a substantial gender biased towards females. Adding a charity recipient to the possible choices, the charity becomes the primary recipient and overall transfers increase. Yet, conditioning on transfers to fellow students the gender bias of women remains. Moreover, we find that women tend more towards giving half the endowment while men tend more towards “all or nothing.” The literature on cognitive dissonance (the feeling of distress once we act against our internalised values) emphasises the importance of voluntary choice for dissonance effects to take hold. Accordingly, we interpret our results as hinting at an important detail regarding the ongoing debate about gender differences in altruistic giving: primary differences may not be found in the amount of transfers made but rather in the choice of the beneficiary's gender.
Keywords: C91; D64; 330; dictator game; gender differences; voluntary choice; charitable giving